Delivery Room Care for Premature Infants Born after Less than 25 Weeks' Gestation-A Narrative Review - Bernhard Schwaberger; Berndt Urlesberger; Georg M. Schmölzer (MDPI AG, 2021)
Premature infants born after less than 25 weeks' gestation are particularly vulnerable at birth and stabilization in the delivery room (DR) is challenging. After birth, infants born after <25 weeks' gestation develop respiratory and hemodynamic instability due to their immature physiology and anatomy. Successful stabilization at birth has the potential to reduce morbidities and mortalities, while suboptimal DR care could increase long-term sequelae. This article reviews current neonatal resuscitation guidelines and addresses challenges during DR stabilization in extremely premature infants born after <25 weeks' gestation at the threshold of viability.